Impact of climate effects on milk production of Holstein cattle in Lima, Peru - Galván Cavero, Gerardo Antonio (2023)
The results of 443 763 periodic controls of daily milk production (DMP) carried out between January 2006 and December 2018 in five Holstein dairy farms in the Lima region were related to meteorological information (maximum and minimum temperature and relative humidity), under temperature-humidity indexes (THI) to represent the current state and the trends of the relationships between DMP and possible thermal stress (TS) identified by the level of THI. The DMP levels along the THI levels showed a response curve with a THI tolerance zone where there is little variation in DMP and threshold point at THI >68 from which DMP is reduced at a rate of -0.413 kg of milk per unit of increase in THI. Analyzed as a whole, this negative response represents an impact of -365 kg of milk per cow per year. It is concluded that all the trends are consistent in pointing out antagonism between TS and DMP, which is a warning call to authorities to take actions to mitigate this effect.